Initiation factor eIF5B catalyzes second GTP-dependent step in eukaryotic translation initiation - Lee, Joon H. (National Academy of Sciences, 2002)
Initiation factors IF2 in bacteria and eIF2 in eukaryotes are GTPases that bind Met-tRNA [Formula: see text] to the small ribosomal subunit. eIF5B, the eukaryotic ortholog of IF2, is a GTPase that promotes ribosomal subunit joining. Here we show that eIF5B GTPase activity is required for protein synthesis. Mutation of the conserved Asp-759 in human eIF5B GTP-binding domain to Asn converts eIF5B to an XTPase and introduces an XTP requirement for subunit joining and translation initiation. Thus, in contrast to bacteria where the single GTPase IF2 is sufficient to catalyze translation initiation, eukaryotic cells require hydrolysis of GTP by both eIF2 and eIF5B to complete translation initiation.